سياسة الهدم في المشرق الإسلامي حتى سنة 132 هـ. / 749 م.: دراسة تاريخية - الازيرجاوى، قاسم جوده عداى (جامعة بغداد - كلية التربية ابن رشد, 2021)
تسلط هذه الدراسة الضوء على سياسة الهدم في المشرق الإسلامي في دولة الرسول محمد (صلى الله عليه وآله)، وفي العصر الراشدي، وفي حكم الدولة الأموية، ويتحدد موضوع الدراسة جغرافيا على شبه الجزيرة العربية، وسوريا (بلاد الشام)، والعراق، أما زمنيا فهو يغطي القرن الأول الهجري، وأربع عقود من القرن الثاني الهجري، موضوع الدراسة لم يسبق التطرق إليه سابقا إلا ما ندر، والهدم يتفرع لمعان عدة، وكلها تقريبا تصب في معنى واحد وهو ضد البناء، ولم يحدد في عنوان البحث ما الشيء المهدوم كونه يتضمن هدم المساجد، والكنائس، والدور، والقصور. وأسباب الهدم كثيرة منها: الدينية، والاجتماعية، والسياسية، وقد أتخذ كوسيلة عقاب بحق المعارضين، وممن يضمر السوء لدولة الإسلام، وقد يكون وراءه تعصب عنصري نبذه الإسلام، أو رفض تزويج، والهدم ذو الأسباب السياسية طغى على مادة البحث، وبدأ في خلافة الإمام علي (عليه السلام)، وتصاعدت وتيرته في عصر الدولة الأموية، وأستخدمه المختار الثقفي، وكوسيلة عقاب لكل من شارك في قتل الإمام الحسين (عليه السلام) في كربلاء. كما أستخدمه ولاة، وقادة جيوش بني أمية بحق معارضيهم، كما أستخدمه أيضا دعاة بني العباس في أثناء ثورتهم على الحكم الأموي.
This study sheds light on the policy of demolition in the Islamic East in the state of the Prophet Muhammad (peace be upon him), and in A1-Rashidi age, and in the rule of the Umayyad state, The subject of the study is determined geographically on the Arabian Peninsula, Syria (A1-Sham) country, and Iraq, but in time it covers the first century And four decades from the second century AH. The subject of the study was not previously touched upon except rarely. The word demolition has several meanings, and almost all of them pour in one meaning, it is against construction. It did not specify in the title of the research what the demolished object included the demolition of mosques, churches, houses and palaces The reasons for the demolition are many, including religious and social ones. They are approved. It has been taken as a punishment against opponents, and those who harbor ill-treatment for the state of Islam It may be motivated by racial intolerance that is rejected by Islam, or refused to marry. The demolition of political reasons overwhelmed the subject of research, and began to succeed Imam Ali (peace be upon him). It escalated in the era of the Umayyad state, and was used by Mukhtar bin Obaidullah Althaqfy, and as a means of punishment for all those who participated in the killing of Imam Hussein as) in Karbala. It was also used by the governors and the leaders of the armies of the Umayyad son against their opponents. It was also used by the preachers of Bani Abbas during their revolution against the Umayyad rule.
Keywords: الهدم -- سياسة الهدم -- المشرق الإسلامي -- العهد النبوي -- العهد الراشدي -- الدولة الأموية